Insights from genomic studies on the role of sex steroids in the aetiology of endometriosis - Philippa T K Saunders (Bioscientifica, 2022)
Endometriosis is a chronic neuro-inflammatory disorder the defining feature of which is the growth of tissue (lesions) that resembles the endometrium outside the uterus. Estimates of prevalence quote rates of ~10% of women of reproductive age, equating to at least 190 million women world-wide. Genetic, hormonal and immunological factors have all been proposed as contributing to risk factors associated with the development of lesions. Twin studies report the heritable component of endometriosis as ~50%. Genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) that appear over-represented in patients with endometriosis, particularly those with more extensive disease (stage III/IV). In different sample populations, there has been replication of SNPs near genes involved in oestrogen and other steroid regulated pathways including ESR1 (oestrogen receptor alpha), GREB1, HOXA10, WNT4 and MAPK kinase signalling. Comparisons with GWAS conducted on other patient cohorts have found links with reproductive traits (age at menarche) and disorders (fibroids, endometrial and ovarian cancer) and common co-morbidities (migraine, depression, asthma). In summary, genetic analyses have provided new insights into the hormone-regulated pathways that may contribute to increased risk of developing endometriosis some of which may act in early life. New studies are needed to clarify the relationship between the many SNPs identified, the genes that they regulate and their contribution(s) to development of different forms of endometriosis. We hope that more advanced methods allowing integration between GWAS, epigenetic and tissue expression data will improve risk analysis and reduce diagnositic delay.